ESTIMATION OF INDUSTRIAL WASTE SAFETY BY THE “CHEMICAL OXYGEN DEMAND” INDEX - A. S. Kayshev; N. S. Kaysheva; N. A. Tukhovskaya (Фармация и фармакология (Пятигорск))
One of the indices of industrial waste safety including distillers grains is chemical oxygen demand (COD), and its value (53591÷64184 mg O/dm3) shows that it can be considered as unsustainable waste. This high value of COD is conditioned by the absence of toxins in distillers grains, and by concentration of biologically active substances after which isolation the distillers grains index lowers by 74%. This allows considering the distillers grains as environmentally safe. The results received evidence the necessity for consideration of COD index only as an index of oxidized substances, but not the criteria of waste pollution.